A study to assess the effect of video assisted teaching programme on knowledge regarding child abuse among school children in a selected school of West Bengal - Das, Sumitra; Jana, Manasi (International Journal Of Community Medicine And Public Health, 2025)
Background: Every child has a right to a safe childhood and a life free from brutality. The experience of child abuse and neglect contravene upon that right. Child abuse is the state of emotional, physical, economical and sexual maltreatment to a person below the age of 18 years and is a globally prevalent phenomenon. Child abuse is a global issue affects children of all ages, gender, races, ethnicities, in varied socioeconomic classes and is in the vanguard in the line of widespread social issues and social problems. Education regarding child abuse for children is very important to promote all round development of children. Methods: In this pre-experimental one group pre-test post-test research study to evaluate the effect of video assisted teaching programme on knowledge regarding child abuse was conducted among 100 school children of Basunagar High School (H.S.), North 24 Parganas from 06 March 2023 to 31 March 2023 were selected by non- probability convenience sampling technique. Demographic and general information collection tool and structure knowledge questionnaire were used for data collection. Results: The study finding revealed that the mean post-test score was 14.66 which was higher than mean of pre-test 4.57. It was revealed that mean difference between post-test and pre-test knowledge score was found to be statistically significant t (1.985), df-99, p<0.05 which indicate the effectiveness of structured teaching programme on child abuse and there was a significant association of pre-test knowledge score with age monthly income of family, occupation of father, type of house (p<0.05). Conclusions: From the study findings it is concluded that the provision of video assisted teaching programme helps to motivate the school children to learn and also to improve their knowledge level regarding child abuse.